Characterization of Radioactivity Contaminated Sites in Thi-Qar Governorate - Nazar A.Husein; Murtada A.Sayah; Falah SH. Hussein; Alaa H. Muhsen; Basem H. Essa (Journal of Madenat Alelem University College, 2020)
Radioactive contamination occurred in different areas in several locations of the province of Thi Qar as a result of the use of the alliance ammunition depleted uranium forces shelled civilian targets and military during the 1991 Gulf War, as well as in 2003 and have been some of the sites to address during the year 2008 by the Ministry of Science and Technology and the Department of Environment Thi Qar and radiation protection center and through contaminated military pieces and packaged and transported to the quarry which was chosen in 2007 and the approval of the Directorate of Thi Qar province, environment and prevention center of radiation and were transferred amount of contaminated soil aggregation (estimated at up to 3 tons ) and cut the number of military scrap, which was taken at the time amounted to 31 pieces of various sizes and geometric shapes.When a radiation survey in different areas of the province of Thi Qar, especially the areas that were the scene of military operations in 2003, it was revealed the presence of radioactive contamination at three sites for power plants, the Southwest and northern networks circle and rural stores in Thi Qar province due to shelling hardware to depleted uranium by the US bombing 2003 where contaminated by releases of depleted uranium, a number of electrical transformers and walls and columns of concrete and iron in addition to the contamination of the ground in the networking site due to decomposition releases depleted uranium that may have collided with columns of concrete or iron and fell on the land site, which accelerated in the process of degradation and the spread of depleted uranium in the soil of the site.So, This  research aims to identify contaminated areas and pieces the amount of contamination found in the military or civilian vehicles and put them on the radiological map of environmental for the purpose of developing and identifying appropriate methods for each site treatment by the size of the mechanisms and space pollution in order to protect the environment and the population in those areas of the health risks and to prevent the continued spread of this pollution and to ensure that these contaminated transmission mechanisms to other sites.